2018
DOI: 10.1111/apa.14218
|View full text |Cite
|
Sign up to set email alerts
|

Dog bites in a U.S. county: age, body part and breed in paediatric dog bites

Abstract: Dog bites occur with higher frequency at younger ages, and head and neck injuries are more common in younger children. Pit bull bites are more common in adolescents and Shih-Tzu bites more common in younger children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 23 publications
9
33
0
Order By: Relevance
“…Ramgopal et al. reviewed the characteristics of 14 956 dog bites reported to the Allegehny County Health Department in the USA between 2007 and 2015 by the child's gender, age and body part and by the breed of the dog . They found that dog bites were more frequent in boys and in younger children, who were particular affected by head and neck injuries.…”
Section: Paediatric Dog Bitesmentioning
confidence: 99%
“…Ramgopal et al. reviewed the characteristics of 14 956 dog bites reported to the Allegehny County Health Department in the USA between 2007 and 2015 by the child's gender, age and body part and by the breed of the dog . They found that dog bites were more frequent in boys and in younger children, who were particular affected by head and neck injuries.…”
Section: Paediatric Dog Bitesmentioning
confidence: 99%
“…Massive bleeding associated with wounds in infants warrant emergency intervention. The major risk factors for dog bites involving the head or neck injuries include younger age, male sex, and a breed of dogs with a proclivity for biting; unfortunately patient 1 had these risk factors, but the family did not take any preventive measuresFurthermore, patient 2 was bitten on his extremities previously, which is major a risk factor for cat bites, and hence the cat needed to be prevented from getting close to the infant . Although counseling children and families about preventable pet‐related injury is beneficial, the actual rate of providing guidance is low .…”
mentioning
confidence: 99%
“…Although counseling children and families about preventable pet‐related injury is beneficial, the actual rate of providing guidance is low . Another problem is that it is the owner's responsibility to report animal bites only to local public health center in Japan, whereas in the USA animal bites are required to be reported to state boards of health . We also experienced that the animal injuries sustained occurred regardless of witness being present.…”
mentioning
confidence: 99%
See 2 more Smart Citations